Predicting late-onset sepsis by routine neonatal screening for colonisation by gram-negative bacteria in neonates at intensive care units: a protocol for a systematic review. Issue 3 (29th March 2017) - Harder, Thomas; Seidel, Juliane; Eckmanns, Tim; Weiss, Bettina; Haller, Sebastian
Abstract : Introduction: Hospitals conduct extensive screening procedures to assess colonisation of the body surface of neonates by gram-negative bacteria to avoid complications like late-onset sepsis. However, the benefits of these procedures are controversially discussed. Until now, no systematic review has investigated the value of routine screening for colonisation by gram-negative bacteria in neonates for late-onset sepsis prediction. Methods and analysis: We will conduct a systematic review, considering studies of any design that include infants up to an age of 12 months. We will search MEDLINE and EMBASE (inception to 2016), reference lists and grey literature. Screening of titles, abstracts and full texts will be conducted by two independent reviewers. We will extract data on study characteristics and study results. Risk of bias will be assessed using Quality Assessment of Diagnostic Accuracy Studies (QUADAS-2) and Quality in Prognosis Studies (QUIPS) tools. Subgroup analyses are planned according to characteristics of studies, participants, index tests and outcome. For quantitative data synthesis on prognostic accuracy, sensitivity and specificity of screening to detect late-onset sepsis will be calculated. If sufficient data are available, we will calculate summary estimates using hierarchical summary receiver operating characteristics and bivariate models. Applying a risk factor approach, pooled summary estimates will be calculated as relative risk or OR, using fixed-effects and random-effects models. I-squared will be used to assess heterogeneity. All calculations will be performed in Stata V14.1 (College Station, Texas, USA). The results will be used to calculate positive and negative predictive value and number needed to be screened to prevent one case of sepsis. Grading of Recommendations Assessment, Development and Evaluation (GRADE) will be used to assess certainty in the evidence. The protocol follows the Preferred Reporting Items for Systematic Review and Meta-Analysis Protocols (PRISMA-P) guideline. Ethics and dissemination: This study will not require ethical approval since it is not carried out in humans. The systematic review will be published in an open-access peer-reviewed journal. Trial registration number: CRD42016036664.